A Novel Approach for Skin Regeneration by a Potent Bioactive Placental-Loaded Microneedle Patch: Comparative Study of Deer, Goat, and Porcine Placentas - Kritsanaporn Tansathien; Phuvamin Suriyaamporn; Tanasait Ngawhirunpat; Praneet Opanasopit; Worranan Rangsimawong (MDPI AG, 2022)
The aims of this study were to investigate the skin regeneration potential of bioactive placenta (deer placenta (DP), goat placenta (GP), and porcine placenta (PP)) and fabricate bioactive extract-loaded dissolving microneedles (DMNs) as a dermal delivery approach. The placentas were water-extracted, and the active compounds were evaluated. Bioactivity studies were performed in dermal fibroblasts and keratinocytes. DMNs were fabricated to deliver the potent bioactive placenta extract into the skin. All placental extracts expressed high amounts of protein, growth factors (EGF, FGF, IGF-1 and TGF-β1), and amino acids. These extracts were not toxic to the skin cells, while the proliferation of fibroblast cells significantly increased in a time-dependent manner. GP extract that exhibited the maximum proliferation, migration, and regeneration effect on fibroblast cells was loaded into DMN patch. The suitable physical properties of DMNs led to increased skin permeation and deposition of bioactive macromolecules. Moreover, GP extract-loaded DMNs showed minimal invasiveness to the skin and were safe for application to human skin. In conclusion, placental extracts act as potent bioactive compounds for skin cells, and the highest bioactive potential of GP-loaded DMNs might be a novel approach to regenerate the skin.